Karakteristik Mikroemulsi Yang Mengandung Ekstrak Virgin Coconut Oil (Vco) Bawang Dayak (Eleutherine Palmifolia ) - Rubbana Sunardi; I Dewa Gde Mayun Permana; Lutfi Suhendra (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2021)
This study aims was to determine the effect of the comparison of Dayak onions with VCO and the length of time of maceration on the characteristics of Dayak onion extract, was to get the best ratio of Dayak onions toVCO and the length of time of maceration so that the dayak extract with the best characteristics is produced, to determine the effect of the ratio of surfactants with VCO dayak extract. on the characteristics of the O/Wmicroemulsion, as well as getting the right ratio of the surfactant and VCO Dayak extract so that a stable O / W microemulsion was produced. This research was conducted in two steps. The first stage was the optimizationof the ratio of the material to the solvent and the length of time for maceration. The first stage, the experimental design used was a factorial randomized block design consisting of 2 factors, namely the first factor was thecomparison of Dayak simplicia with VCO solvent (1: 3, 1: 5, 1: 7, 1: 9, 1:11) . The second factor was the length of maceration (5, 7, and 9 hours). The best research result in the first stage are used in the second stageof research. The second stage was optimization of the microemulsion of Dayak's VCO extract. The experimental design used was a completely randomized design. In the treatment of the surfactant ratio withDayak onion VCO extract (89:11, 87:13, 85:15, 83:17, and 81:19 (v / v)). The data obtained were analyzed using variance fingerprints, and if there was an effect of treatment on the observed variables, it was followedby Tukey's 95% test. The best research result in the first stage were obtained in the treatment of the simplicia ratio of Dayak onions and VCO solvent (1:11) and maceration time of 9 hours with a total carotenoid contentof 17.915 (µmol / L), brightness (L *) 58.70, redness (a * ) 13.60, yellowish (b *) 74.45. The results of the second stage obtained a comparison of surfactants and dayak onion VCO extract (85: 15 v / v) with theturbidity index value of centrifugation (0.510), heating (0.507), pH 3.5, dilution 1: 9; 1:49 and 1:99 (0.121; 0.096; and 0.083), pH 4.5, dilution 1: 9; 1:49 and 1:99 (0.096; 0.088; and 0.078), pH 6.5, 1: 9 dilution; 1:49and 1:99 (0.093; 0.084; and 0.071), as well as storage with a microemulsion slope value of 0.0742 o/w.